Examining Diagnostic Options and Classification Systems Available for Endometriosis - Debabrata Ghosh; Jayasree Sengupta (European Medical Journal Reproductive Health, 2021)
Introduction: Endometriosis is characterised by the presence of endometrium-like tissue outside the uterus, and is often associated with chronic pelvic pain, infertility, and compromised quality of life. Development of reliable methods of early diagnosis, staging, and classification of endometriosis would allow for restriction of disease progression by its early detection and strategising towards its early treatment and management.